Study of Grain Boundary Character - Tanski, Tomasz; Borek, Wojciech (IntechOpen, 2017)
This book contains eight chapters with original and innovative research studies in the field of grain boundaries. The results presented in the chapters of this book are very interesting and inspiring. This book will be very valuable to all researchers who are interested in the influence of grain boundaries on the structure and different kinds of properties of engineering materials. This book is also addressed to students and professional engineers working in the industry as well as to specialists who pay attention to all aspects related to grain boundaries and their impact on the various properties of innovative materials. The chapters of this book were developed by respected and well-known researchers from different countries.